Evaluation of Olfactory Fossa Keros Classification Using CT scans, A Hospital-Based Study - Ayad Faraj Rasheed (Advanced Medical Journal)
Background and objectives: Prior to any surgery for sinonasal diseases, a preliminary scanning of the paranasal sinus is required to validate that the surgical approach is satisfactorily planned and to avoid complications connected to the anatomy of this area. We intended to assess the olfactory fossa depth using paranasal sinus CT images to identify the types and prevalence of Keros classification in our population.